2023
DOI: 10.21203/rs.3.rs-2648373/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Central Venous Catheter Thoracic Drainage with Traditional Closed Thoracic Drainage after Minimally Invasive Surgery for Esophageal Cancer: A Retrospective Study

Abstract: Background To compare the effectiveness and safety of central venous catheter thoracic drainage (CVC-TD) with traditional closed thoracic drainage (TCTD) after minimally invasive surgery for esophageal cancer. Methods We conducted a retrospective study of 103 patients who underwent minimally invasive surgery for esophageal cancer at our institution between January 2017 and December 2019. Forty-four patients received CVC-TD, while 59 patients received TCTD. We compared the following outcomes between the two g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Patients with severe anastomotic leakage had an extremely poor prognosis [37]. Several studies had reported that various methods of chest drainage following esophageal cancer surgery did not affect the incidence of anastomotic leakage [8][9][10][11]38]. This finding was consistent with our study, which showed that the incidence of postoperative anastomotic leakage in patients in the MD group was not statistically different from the other two groups.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with severe anastomotic leakage had an extremely poor prognosis [37]. Several studies had reported that various methods of chest drainage following esophageal cancer surgery did not affect the incidence of anastomotic leakage [8][9][10][11]38]. This finding was consistent with our study, which showed that the incidence of postoperative anastomotic leakage in patients in the MD group was not statistically different from the other two groups.…”
Section: Discussionsupporting
confidence: 90%